Oxidation of p-Cresol by ozonation - Kow, Su-Huan; Muhammad Ridwan Fahmi,; Che Zulzikrami Azner Abidin,; Ong, Soon-An; Abdul Haqi Ibrahim,; Siti Nasuha Sabri,; Nur Aqilah Razali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Oxidation of p-Cresol was investigated by using ozonation process. The aim of this research is to assess the effectiveness of ozonation on oxidation of micropollutant such as p-Cresol. Ozonation performance was evaluated based on p-Cresol concentration reduction and chemical oxidation demand (COD) reduction. It was found ozonation at pH11 achieved the highest p-Cresol degradation, with 95.8% of p-Cresol reduced and 96.0% of COD reduced, for an initial 50 mgL-1 of p-Cresol. The degradation of p-Cresol could be expressed by second-order of kinetic model. The second-order rate constant k increases as the initial pH increased, but decreases with the increasing of initial p-Cresol concentrations. Besides, the absorption spectra of p-Cresol over ozonation time were analyzed by spectrophotometry. The evolution of absorption spectra of p-Cresol degradation suggests that the oxidation of p-Cresol follows three stages mechanisms with cycloaddition as the first step to produce aromatic intermediates followed by ring-opening reactions, degradation of the intermediates, and subsequently achieved mineralization.